The Determinant Of Cash Holding - Dini Wahjoe Hapsari; Nabila Roma Norris (Jurnal Akuntansi, 2022)
This study examines the effect of investment opportunity sets, net working capital, and profitability on cash holding. Cash holding is a liquid asset that has the benefits of supporting the company in the company's routine operational activities. The application of cash holding in a company can be influenced by investment opportunities, net working capital, and profitability. From 2016 to 2021, the research population consists of food and beverage companies listed on the Indonesia Stock Exchange. The research sample uses purposive sampling, so there are 15 companies. The study uses secondary data by collecting the company's annual report the data analysis method used in Panel Data Regression utilising the Eviews version 9 application. The results indicate that the investment opportunity set, net working capital, and profitability simultaneously affect cash holding. Partially, only the location of investment opportunities affects cash holding. Meanwhile, net working worth and profitability do not affect cash holding.